Salinity response function on groundnut crop yield for Coastal region in Gujarat - PANDYA, SHRADHDHA; SUBBAIAH, R. (Journal of Soil and Water Conservation, 2020)
Water scarcity and salinity are major constrains for agricultural sector in arid and semi-arid regions. Seasonally fluctuations in salt concentration of irrigation water effect on crop yield. Hence in the present effort the influence of variable concentrations of irrigation water subjected to groundnut crop and its effect was assessed on crop yield response by undertaking a field experiment during 2015. Four different concentration of saline irrigation water mainly 2 dSm-1 (T1), 4 dSm-1 (T2), 8 dSm-1 (T3) and 12 dSm-1 (T4) applied to vegetative stage (S1), flowering stage (S2) and pod development stage (S3), treatments were replicated four times. Threshold irrigation water salinity level was found to be 2 dSm-1 at each stage. FAO approach failed to predict concentration of irrigation water at which relative yield becomes zero accurately. The salinity of irrigation water at which yield become zero was estimated for different stages as per the procedure developed in the present study. Developed approach for yield response to differential salinity at different stages represented with a 3rd or 4th order polynomial equation. Based on different concentration of saline water, concluded that for each stage, yield decreases continuously while salinity increases above threshold level.